Pengaruh Kenakalan Remaja Terhadap Peningkatan Pernikahan Dini pada Masa Covid 19 di Kecamatan Ajung - Nikmah, Herlina Hidayatun; Adila, Khalisa; Fitriana, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2022)
Marriage is a promise binding ceremony that is celebrated or carried out by two people with the intention of formalizing the marriage bond according to religious norms, legal norms, and social norms. Early marriage is carried out by someone who has a relatively young age, so that can be said to be early marriage. The relatively young age referred to is the age of puberty, namely the age between 10-19 years. In this study, researchers used quantitative research methods. The results of the data obtained resulted in a calculation of 0.001 which means significant data, which indicates that the variables in this study can be tested and there is a link between the influence of juvenile delinquency on the increase in early marriage.